1995
DOI: 10.1055/s-0038-1649846
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Inhibition of Tissue Factor-Factor Vila by Tissue Factor Pathway Inhibitor

Abstract: SummaryTissue factor-factor VIIa catalysed activation of factor X and factor IX is inhibited by the complex of tissue factor pathway inhibitor (TFPI) and factor Xa. At present, no information is available as to what extent the kinetics of complex formation between TFPI and factor Xa during factor X activation contribute to the overall rate of inactivation of the factor X converting complex. We have determined the kinetic parameters of the individual reactions, i. e. factor X activation, formation of the TFPI-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 6 publications
5
48
0
Order By: Relevance
“…All three sets of analyses consistently required values of k INH, VIIa⅐TF in excess of 10 8 M Ϫ1 ⅐s Ϫ1 for adequate description (Table I). Interestingly, the values for k INH,VIIa⅐TF determined by numerical analyses are in remarkable agreement with the same rate constant inferred from kinetic studies of VIIa⅐TF inhibition during X activation using picomolar concentrations of Xa and TFPI (22).…”
Section: Regulation Of Factor X Activation By Tfpisupporting
confidence: 82%
See 2 more Smart Citations
“…All three sets of analyses consistently required values of k INH, VIIa⅐TF in excess of 10 8 M Ϫ1 ⅐s Ϫ1 for adequate description (Table I). Interestingly, the values for k INH,VIIa⅐TF determined by numerical analyses are in remarkable agreement with the same rate constant inferred from kinetic studies of VIIa⅐TF inhibition during X activation using picomolar concentrations of Xa and TFPI (22).…”
Section: Regulation Of Factor X Activation By Tfpisupporting
confidence: 82%
“…However, since inhibition of both factor Xa and VIIa⅐TF by physiological (nanomolar) concentrations of TFPI is not instantaneous, the regulation of this pathway is likely to be heavily influenced by the kinetics determining the individual steps. Although the individual reactions of TFPI have been studied by a number of groups, there is uncertainty as to which inhibition reaction corresponds to the rate-limiting step (21,22). In addition, the effects of TFPI on active factor Xa formation by the extrinsic pathway have not been experimentally documented.…”
Section: ؊1mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of TFPI on TF⅐FVIIa activity in the absence of FXa is negligible (21,22), implying that the true inhibitor of TF⅐FVIIa activity is the FXa⅐TFPI complex. The rate of complex formation of FXa and TFPI is enhanced by negatively charged phospholipids for full-length TFPI (TFPI FL ) but not for TFPI 1-161 , a truncated variant lacking the third Kunitz domain and the potential phospholipid binding C-terminal tail (16,23).Recently (24), we demonstrated that TFPI FL in complex with FXa has a much higher affinity for anionic phospholipid membranes compared with that of either protein alone. It is well recognized that the binding of blood coagulation enzymes as well as their cofactors and substrates to membranes containing anionic phospholipids may result in an immense increase of the catalytic efficiency of these enzymes.…”
mentioning
confidence: 99%
“…The effect of TFPI on TF⅐FVIIa activity in the absence of FXa is negligible (21,22), implying that the true inhibitor of TF⅐FVIIa activity is the FXa⅐TFPI complex. The rate of complex formation of FXa and TFPI is enhanced by negatively charged phospholipids for full-length TFPI (TFPI FL ) but not for TFPI , a truncated variant lacking the third Kunitz domain and the potential phospholipid binding C-terminal tail (16,23).…”
mentioning
confidence: 99%